2014
DOI: 10.1186/s12963-014-0023-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of record linkage of mortality data between a health and demographic surveillance system and national civil registration system in South Africa

Abstract: Background: Health and Demographic Surveillance Systems (HDSS) collect independent mortality data that could be used for assessing the quality of mortality data in national civil registration (CR) systems in low-and middle-income countries. However, the use of HDSS data for such purposes depends on the quality of record linkage between the two data sources. We describe and evaluate the quality of record linkage between HDSS and CR mortality data in South Africa with HDSS data from Agincourt HDSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
(51 reference statements)
1
10
0
Order By: Relevance
“…This analysis suggests that approximately 95% of adult deaths with IDs in South Africa are recorded through the vital registration system, which is similar to recent estimates obtained using DDMs [ 13 – 15 ] and a 94% completeness among individuals with IDs in a demographic surveillance site [ 35 ]. Although this consistency with DDM estimates is reassuring, this analysis raises concern about one of the central assumptions of DDMs, namely that the completeness of death reporting is constant with respect to age in adults [ 11 ].…”
Section: Discussionsupporting
confidence: 86%
“…This analysis suggests that approximately 95% of adult deaths with IDs in South Africa are recorded through the vital registration system, which is similar to recent estimates obtained using DDMs [ 13 – 15 ] and a 94% completeness among individuals with IDs in a demographic surveillance site [ 35 ]. Although this consistency with DDM estimates is reassuring, this analysis raises concern about one of the central assumptions of DDMs, namely that the completeness of death reporting is constant with respect to age in adults [ 11 ].…”
Section: Discussionsupporting
confidence: 86%
“…Out of the 1,001 deaths recorded in the population, only 187 could be matched by name in hospital registers (38). Another recent attempt conducted in 2006–2009 showed that there was no major bias in death registration between HDSS and CRVS in the Agincourt area, demonstrated that 60.8% of death records could be matched using complex procedures, and confirmed that those that could not be matched were mostly the deaths of young children, those in poorer households, and Mozambicans, most likely because these deaths did not occur in hospitals and were never registered (41). …”
Section: Discussionmentioning
confidence: 99%
“…As a pilot, prior to the first round of HBT (HBT‐R1) a standard deterministic and probabilistic record‐linkage was conducted in order to match the HDSS individuals simple randomized for HBT and the Manhiça hospital ePTS records for those already enrolled in care.…”
Section: Methodsmentioning
confidence: 99%